2015
DOI: 10.1542/hpeds.2014-0232
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Skin and Soft Tissue Infection in Infants 90 Days Old or Younger

Abstract: A B S T R A C T BACKGROUND AND OBJECTIVES:Skin and soft tissue infections (SSTIs) are an increasingly common cause of pediatric hospital visits among infants. The optimal evaluation strategy for younger infants with SSTI is unknown because there is little information about outcomes including risks of concomitant bacterial infections and treatment failure. This study was designed to determine rates of concomitant invasive bacterial infection and hospital revisits for treatment failure as well as factors associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…For example, fever was not reliably coded in our study, and compared with other similar investigations, assignment of ICD-9-CM codes for fever was low. 5 Lack of reliable fever coding limits our ability to examine the impact of fever on antibiotic prescribing and limits our ability to make any recommendations regarding the appropriate treatment of SSTI in the setting of fever. The use of an administrative data set also limits our ability to evaluate the association of patient presentation with clinical decision-making.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, fever was not reliably coded in our study, and compared with other similar investigations, assignment of ICD-9-CM codes for fever was low. 5 Lack of reliable fever coding limits our ability to examine the impact of fever on antibiotic prescribing and limits our ability to make any recommendations regarding the appropriate treatment of SSTI in the setting of fever. The use of an administrative data set also limits our ability to evaluate the association of patient presentation with clinical decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Infants were considered for inclusion on the basis of the presence of an ICD-9-CM principal diagnosis for an SSTI, including cellulitis, abscess, carbuncle, furuncle, or mastitis (Supplemental Table 4). [2][3][4][5]17,18 If an infant had multiple hospitalizations within a 30-day period, only the first hospitalization was considered an index admission; subsequent ED revisits or hospitalizations were considered returns and were defined as same-, related-, or all-cause returns.…”
Section: Study Population Inclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical presentation and outcome of our newborns with PSSTI were consistent with other skin and soft-tissue infections in this age group. 4,5 Importantly, these cases were distinct from omphalitis, an infection of the umbilical remnant, which is usually polymicrobial and is often associated with significant clinical morbidity and may even be lethal. 6,7 In this disease, the umbilical cord itself may be a portal of entry for infection and when combined with necrotic tissue and/or thrombosed vessels may provide access to bloodstream.…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of bacterial infection in febrile infants has led clinicians, perhaps reflexively, to manage afebrile infants age 60 days old or younger with skin and soft tissue infections in a similar manner. Prior studies have demonstrated that the majortity of these afebrile infants with skin and soft tissue infections undergo extensive testing even though the prevalence of invasive bacterial infection is as low as 0%, but the small sample sizes of these investigations have resulted in imprecision for these prevalence estimates. Therefore, it is reasonable practice for clinicians to evaluate for bacteremia in well‐appearing afebrile infants with cellulitis or abscesses pending a large, multicenter investigation …”
mentioning
confidence: 99%